Homocysteine modulates CXCL10/CXCR3 axis activity to induce endothelial dysfunction: Hcy affects endothelial dysfunction - Xu, Yanjie; Xu, Yingying; Yu, Zuozong; He, Dingwen (Cellular and Molecular Biology, 2024)
Elevated homocysteine (Hcy) levels have been linked to the development of cardiovascular diseases, notably endothelial dysfunction, a critical precursor to atherosclerosis. In this extensive investigation, we explore the intricate pathways through which Hcy influences endothelial dysfunction, with particular attention to the CXCL10/CXCR3 axis. Employing a dual approach encompassing both in vitro and in vivo models, we scrutinize the repercussions of Hcy exposure on endothelial functionality. Our results reveal that Hcy significantly impairs crucial endothelial processes, including cell migration, proliferation, and tube formation. Concomitantly, Hcy upregulates the expression of adhesion molecules, exacerbating endothelial dysfunction. In a murine hyperhomocysteinemia (HHcy) model, we observed a parallel increase in plasma Hcy levels and adverse vascular effects. Moreover, our study unraveled a pivotal role of the CXCL10/CXCR3 axis in Hcy-induced endothelial dysfunction. Hcy exposure led to the upregulation of CXCL10 and CXCR3, both in vitro and in HHcy mice. Importantly, the blockade of this axis, achieved through specific antibodies or NBI-74330, mitigated the detrimental effects of Hcy on endothelial function. In conclusion, our findings illuminated the central role of the CXCL10/CXCR3 axis in mediating Hcy-induced endothelial dysfunction, providing valuable insights for potential therapeutic strategies in managing HHcy-related cardiovascular diseases.